Duties of legal practitioners and challenges of legal practice in Nigeria (2019)
The thrust of this paper is to appraise the duties of legal practitioner and various challenges confronting legal practice in Nigeria. The pertinent questions which this paper seeks to interrogate are: What is the origin of legal profession in Nigeria? What are the duties and responsibilities of legal practitioners in the society? What is the code of ethics for legal practitioners? What are various challenges confronting legal practice in Nigeria? To resolve these questions, the paper traces the evolution of legal profession in Nigeria. The paper highlights various duties of legal practitioner to his clients and various challenges confronting legal practice in general. The paper concludes with a recommendation among others that a legal practitioner must keep abreast of ethical principles and be creative in the application of his knowledge of legal principles to solve legal issues and real life problems professionally.